Beyond Capital: Ineffective Training and Mentoring in Zakat MSMEs: Z-Mart South Sumatra Case - Ledy Permata Sari; Emi Yulia Siska (Journal Of Economic Cluster, 2025)
This study aims to analyze the influence of productive zakat empowerment on the development of MSMEs (a case study of Z-Mart BAZNAS South Sumatra Province). The population and sample in this study were all mustahik recipients of productive zakat assistance from the Z-Mart BAZNAS South Sumatra Province program, totaling 50 people. The analysis technique used was multiple regression with t-tests and F-tests. The results indicate that capital assistance significantly influences the development of Z-Mart MSMEs. In contrast, training and mentoring variables individually do not influence MSME development, although simultaneously, capital assistance, training, and mentoring affect the development of Z-Mart MSMEs. Based on these findings, this study suggests the need for an overhaul of the training curriculum and mentoring mechanisms to better align with the specific technical needs of the mustahik.